ModEM: A modular system for inversion of electromagnetic geophysical data - Kelbert, Anna; Meqbel, Naser; Egbert, Gary D.; Tandon, Kush (Computers & geosciences, 2014)
We describe implementation of a modular system of computer codes for inversion of electromagnetic geophysical data, referred to as ModEM. The system is constructed with a fine level of modular granularity, with basic components of the inversion – forward modeling, sensitivity computations, inversion search algorithms, model parametrization and regularization, data functionals – interchangeable, reusable and readily extensible. Modular sensitivity computations and generic interfaces to parallelized inversion algorithms provide a ready framework for rapid implementation of new applications or inversion algorithms. We illustrate the code׳s versatility and capabilities for code reuse through implementation of 3D magnetotelluric (MT) and controlled-source EM (CSEM) inversions, using essentially the same components. •Parallel 2D and 3D magnetotelluric modeling and inversion tool.•Extensible to most electromagnetic data types.•Provides generic inversion and modular sensitivity computations.•Provides templates for rapid development of new applications.•Free for academic use.